1984
DOI: 10.1161/01.cir.69.5.895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of persistent obesity in children on cardiovascular risk factors: the Bogalusa Heart Study.

Abstract: The relationship between body fat indexes, lipid and lipoprotein levels, and blood pressure was studied in 2230 children, each examined during 1973, 1976, and 1978. The children were grouped with the use of seven percentile (P) intervals of triceps skinfold thickness that were specific for race, sex, and age; cardiovascular risk factor variables were assessed over time. Of the 238 children initially in the lowest P group (<15P), 44% remained there, and 65% had skinfold thicknesses below 30P on the three occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0
3

Year Published

1985
1985
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 28 publications
1
59
0
3
Order By: Relevance
“…However, obesity not only persists from infancy into adulthood, but has been associated with an unfavourable cardiovascular risk profile in the first 20 y of age. 5,6 These studies suggest that childhood is a key period to identify those at risk of becoming obese adults. The development of obesity may start during the adolescent growth spurt period, which is one of the critical periods for the development of obesity identified by Dietz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, obesity not only persists from infancy into adulthood, but has been associated with an unfavourable cardiovascular risk profile in the first 20 y of age. 5,6 These studies suggest that childhood is a key period to identify those at risk of becoming obese adults. The development of obesity may start during the adolescent growth spurt period, which is one of the critical periods for the development of obesity identified by Dietz.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies of adolescents only report menarche. 5,8 Childhood nutritional stunting, usually an indicator of chronic malnutrition 9,10 and undernutrition, 1,11 has been suggested as a contributory factor to elevated rates of obesity (high weight-for-height) in developing countries. This association between stunting and adolescent and adult obesity has been investigated in several other studies.…”
Section: Introductionmentioning
confidence: 99%
“…Reports from the Bogalusa Heart study showed positive associations between obesity in childhood and/or adolescence and cardiovascular risk factors at young adulthood. [23][24][25] In addition, recent reports showed that childhood obesity was positively related to cardiovascular mortality years hereafter. [26][27][28] However, information on the relationship between adolescent BMI and cardiovascular risk as estimated by measurement of common CIMT in young adulthood is limited, 29 let alone information concerning change in BMI over time and alterations in vascular architecture.…”
Section: Introductionmentioning
confidence: 99%
“…10 ± 16 In fact, there is substantial evidence suggesting that obesity in childhood lays the metabolic groundwork for adult cardiovascular disease. 10,13 Also, many studies demonstrate that overweight children tend to become overweight adults. 17 ± 20 Overall, obesity in childhood appears to increase the risk of subsequent morbidity, whether or not obesity persists into adulthood.…”
Section: Introductionmentioning
confidence: 99%